Focused multidimensional scaling: interactive visualization for exploration of high-dimensional data - Urpa, Lea M.; Anders, Simon (BMC bioinformatics, 2019)
Visualization is an important tool for generating meaning from scientific data, but the visualization of structures in high-dimensional data (such as from high-throughput assays) presents unique challenges. Dimension reduction methods are key in solving this challenge, but these methods can be misleading- especially when apparent clustering in the dimension-reducing representation is used as the basis for reasoning about relationships within the data.